2017
DOI: 10.1002/adsu.201600032
|View full text |Cite
|
Sign up to set email alerts
|

From an Enhanced Understanding to Commercially Viable Electrodes: The Case of PTCLi4 as Sustainable Organic Lithium‐Ion Anode Material

Abstract: for tomorrow's society. [1][2][3] For this purpose, however, the battery technology itself must become sustainable as well. A great step forward toward this highly desirable goal would be the replacement of currently utilized inorganic electrode compounds, which commonly require energy-intensive synthesis methods and relatively rare metals, by eco-efficient organic lithium storage materials, ideally using biomass as precursors. [4] While this general concept has been proposed as early as the development of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 60 publications
2
42
0
Order By: Relevance
“…In contrast, Iordache et al. demonstrated a hybrid lithium‐ion cell using perylene‐3,4,9,10‐tetracarboxylate as active electrode material, which featured a stable voltage of 1.2 V and an initial capacity of 120 mAh g −1 , losing 25 % over the first 200 cycles . Consequently, the material was also used in a fully organic cell, using a hexyl‐linked perylene diimide polymer as second electrode material .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Iordache et al. demonstrated a hybrid lithium‐ion cell using perylene‐3,4,9,10‐tetracarboxylate as active electrode material, which featured a stable voltage of 1.2 V and an initial capacity of 120 mAh g −1 , losing 25 % over the first 200 cycles . Consequently, the material was also used in a fully organic cell, using a hexyl‐linked perylene diimide polymer as second electrode material .…”
Section: Methodsmentioning
confidence: 99%
“…[102] In contrast,I ordache et al demonstrated ah ybrid lithium-ion cell using perylene-3,4,9,10-tetracarboxylatea sa ctivee lectrode material, which featured as table voltage of 1.2 Vand an initial capacityo f1 20 mAh g À1 ,l osing 25 %o ver the first 200 cycles. [103] Consequently,t he material was also used in a fully organic cell, using ah exyl-linked perylene diimidep olymer as second electrode material. [76] The cell possessed a slightly decreasing discharge voltage with an average at 1.1 V and ac apacity of 75 mAhg À1 ,w hichs howed ar easonable drop to 80 %w ithin the first 200 cycles (Figure14).…”
Section: Other Aromatic Carboxylatesmentioning
confidence: 99%
“…Moreover, the electronic conductivity of perylene tetracarboxylic dianhydride (PTCDA) was further improved by adding conductive additives such as CNTs and reduced graphene oxide (rGO) to achieve higher current densities ,. In addition, lithium salt of perylene tetracarboxylate (Li 4 ‐PTC) has also been reported as anode material for LIBs, which exhibited well‐defined potential plateaus at 1.2 V vs. (Li/Li + ) with negligible polarization and good cyclability ,,. Taking advantage of high potentials of perylene polyimides (cathode) and low potential of its carboxylate derivative (anode), Iordache and coworkers reported a perylene‐based all organic lithium‐ion battery with good cyclability .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, lithium salt of perylene tetracarboxylate (Li 4 ‐PTC) has also been reported as anode material for LIBs, which exhibited well‐defined potential plateaus at 1.2 V vs. (Li/Li + ) with negligible polarization and good cyclability ,,. Taking advantage of high potentials of perylene polyimides (cathode) and low potential of its carboxylate derivative (anode), Iordache and coworkers reported a perylene‐based all organic lithium‐ion battery with good cyclability . Though polymerization of aromatic diimides mitigates its dissolution in the electrolyte effectively, it still causes poor cyclability particularly, at low current densities, possibly due to fragmentation of polyimides into monomers via rupturing of N−N bonds in the polymer chain during electrochemical lithiation/delithiation process .…”
Section: Introductionmentioning
confidence: 99%
“…The latter problem is mainly due to the fact that the functional redox groups need to be connected to conjugated organic cores, which in turn are not redox active but contributes to weight and volume. For SOMs, significant improvement on cycling stability has been achieved with the development of carboxylates following the pioneer work of Tarascon and co‐workers . Special focus has been given to dilithium terephthalate (Li 2 TP), because it can be straightforwardly obtained by recycling polyethylene terephthalate (PET) plastic and can deliver a reversible capacity of 300 mAh g −1 .…”
Section: Introductionmentioning
confidence: 99%